Congenital Heart Defects in Patients with Classic Bladder Exstrophy: A Hitherto Neglected Association? - Promm, Martin; Gerling, Stephan; Schepp, Carsten P.; Rösch, Wolfgang H. (European Journal of Pediatric Surgery, 2021)
Introduction Classic bladder exstrophy (BE) is regarded as an isolated malformation without any further anomalies, but some studies have indicated a higher incidence of cardiac anomalies. This cross-sectional study is planned to evaluate the prevalence of congenital heart defects (CHDs) and the clinical relevance for patients with BE admitted for primary closure.Materials and Methods Patients were prospectively recruited between March 2012 and January 2019. Patients' profiles including demographic data, results of transthoracic echocardiography (TTE), as well as essential peri- and postoperative data were assessed.Results Thirty-nine (25 boys and 14 girls) patients with BE (median age 61 days) underwent delayed primary bladder closure. Thirty-seven (24 boys and 13 girls) patients had received TTE 1 day before surgery. CHD was detected in 7 (18.9%) out of the 39 patients, but no clinical differences between patients with and without CHD were observed peri- or postoperatively.Discussion and Conclusion This prospective systematic evaluation shows an even higher rate of CHD in patients with BE than assumed previously. Although peri- and postoperative outcome did not differ between patients with and without CHD, we consider TTE an important additional method for ensuring a safe peri- and postoperative courses and a short- and long-term care for patients with CHD.
Keywords: bladder exstrophy; congenital heart defects; primary closure